2018
DOI: 10.1002/mrm.27059
|View full text |Cite
|
Sign up to set email alerts
|

Probing the microscopic environment of 23Na ions in brain tissue by MRI: On the accuracy of different sampling schemes for the determination of rapid, biexponential decay at low signal‐to‐noise ratio

Abstract: Voxel-wise T2* determination of Na is feasible in vivo. However, sampling and fitting methods have to be chosen carefully to retrieve accurate results. Magn Reson Med 80:571-584, 2018. © 2018 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 104 publications
(135 reference statements)
5
30
0
Order By: Relevance
“…However as the bi‐exponential model can be envisaged as sampling T2* distribution at two discrete points, the fast and slow T2* estimates should lie reasonably close to mean T2* in voxels with relatively narrow T2* distributions. For example in CSF voxels without partial voluming, a relatively smaller number of compartments are observed and the mean T2* values are reasonably closer to the previous studies . The wide spread of mean T2* distribution in CSF (Figure A) is due to strong partial volume effects present at low resolution, which are also present in GM and WM voxels, as suggested by the large overlap between empirical probability distributions.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However as the bi‐exponential model can be envisaged as sampling T2* distribution at two discrete points, the fast and slow T2* estimates should lie reasonably close to mean T2* in voxels with relatively narrow T2* distributions. For example in CSF voxels without partial voluming, a relatively smaller number of compartments are observed and the mean T2* values are reasonably closer to the previous studies . The wide spread of mean T2* distribution in CSF (Figure A) is due to strong partial volume effects present at low resolution, which are also present in GM and WM voxels, as suggested by the large overlap between empirical probability distributions.…”
Section: Discussionsupporting
confidence: 84%
“…The wide spread of mean T2* distribution in CSF (Figure A) is due to strong partial volume effects present at low resolution, which are also present in GM and WM voxels, as suggested by the large overlap between empirical probability distributions. Given that the mean T2* combines contributions from both fast and slow transverse relaxation components in various compartmentalized motion regimes, the average mean T2* values of 5 ms (WM) and 7 ms (GM) lie expectedly in the range (T2italicshort*, T2italiclong*) derived from previously reported values …”
Section: Discussionmentioning
confidence: 60%
“…It is worth mentioning that recently a number of studies have shown the feasibility of voxel-wise T * 2 mapping in the brain using UTE-3D acquisition techniques. [16][17][18][19][20] However, these techniques were conducted with fewer time points (8-38 echoes), and require long acquisition times (26 min-1 h). Moreover, many of these methods were either done with lower spatial resolution, at a higher magnetic field, or done with both.…”
mentioning
confidence: 99%
“…In multi-echo data acquisitions the time gain allows for faster refocusing and consequently closer echo spacing that is beneficial for the estimation of signal decay parameter, in particular for the short T 2 decay component. 27,37,38 The zG RF -RHE acquisition approach shows image quality improvements across investigated T RO , whereas for shorter T RO an improvement in edge delineation was observed, SNR improvements were found particularly for longer T RO .…”
Section: Discussionmentioning
confidence: 91%